Influence Of Steam Curing On Engineering And Fluid Transport Properties Of High Strength Green Concrete Containing Palm Oil Fuel Ash - Zeyad, Abdullah Mohsen Ahmed (2013)
Previous studies on the utilization of palm oil fuel ash (POFA) in high strength concrete indicated clear limitation in term of the efficiency of the POFA, whereby only small replacement can be used and early strength is significantly reduced in particular at high POFA content. It is envisaged that the efficiency of the POFA could be improved via mechanical and heat treatments. This will enable the POFA to be used in greater volume in high strength concrete, without jeopardizing the properties and performance of the concrete. Thus, the main objective of this investigation is to study the influence of treated palm oil fuel ash (POFA) on the engineering and fluid transport properties of high-strength green concrete (HSGC). In addition, the influence of application of various regimes of steam curing on the engineering and fluid transport properties of the HSGC containing up to 60% of treated POFA is also studied. Effect of treated POFA on its chemical and physical properties has been studied based on tests such as XRD techniques, XRF analysis, SEM/EDX, thermal analysis and particle size analysis. POFA obtained from a palm-oil industry waste was treated via heat treatment to remove excess carbon and ground to a median particle size of about 2 μm. The ultrafine POFA (U-POFA) obtained was then utilized in the production of HSGCs with POFA replacement levels of 0, 20, 40 and 60% by mass of ordinary Portland cement (OPC). The results show that the treatment processes undertaken on the POFA result in a highly efficient pozzolan mineral admixture for HSC and will enable it to be utilized higher quantity.